2014
DOI: 10.26524/14116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Intensity Interval Training On Antioxidants of Male Physical Education Students

Abstract: The purpose of this study is to find out the efficiency of high intensity interval training on antioxidants of male physical education students. To achieve the purpose thirty (30) male physical education students were selected from Swami Vivekanand Subharti University, Department of Physical Education, Meerut, Utter Pradesh. These subjects were tested on antioxidants before and after eight weeks of high intensity interval training (HIIT). The mean maximal aerobic speed 4.21 m/s was used as a criterion velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…One study showed an increase in PGC-1α and no change in SIRT1 levels following a 4-week HIIT with 170% aerobic power [ 31 ]. Also, Hassan et al [ 32 ] concluded that there was a decrease in CAT levels following a 30-week HIIT among 30 active people with the same protocol as in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…One study showed an increase in PGC-1α and no change in SIRT1 levels following a 4-week HIIT with 170% aerobic power [ 31 ]. Also, Hassan et al [ 32 ] concluded that there was a decrease in CAT levels following a 30-week HIIT among 30 active people with the same protocol as in the present study.…”
Section: Discussionsupporting
confidence: 69%